Analisis Penerapan Rotasi Kerja Dalam Upaya Meningkatkan Kinerja Kayawan Pada PT. Chenda Safetyindo Kreasi - Haqiki, Dimas Mausul; S, Sungkono (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Workers are essential organizational resources because they play a key role as the actors and drivers of the organization, carrying out its objectives. This indicates that employee performance has a significant impact on a business's success; as a result, in order to maximize corporate goals, every organization will make an effort to increase staff performance. The purpose of this study is to ascertain, evaluate, and elucidate the impact of work rotation on the enhancement of employee competence as well as the ways in which job rotation enhances employee performance. Interviewing is the method employed, and the outcome is descriptive. In conclusion, the application of job rotation in companies can affect the performance of their employees.